The Impact of Distinctive Root Canal Instrumentation Systems on Endotoxin Lessening from the Root Canal: A Systematic Review and Meta-Analysis - Navid Nasrabadi; Samira Jamali; Marzieh Ghasemi Vojoodi; Marzieh Jamali (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine the impact of distinctive instrumentation systems of the root canals on the endotoxin lessening through the root canals . Material and Methods: From the electronic databases, MEDLINE, PubMed, Cochrane Library, Embase, ISI, Google Scholar have been used to perform a systematic literature review between 2015 and 2020. Therefore, a software program (Endnote X9) has been utilized for managing electronic titles. Searches were performed with keywords, "root canal," "instrumentation," "endotoxin," "root canal preparation," "biofilm" "endodontics," and "lipopolysaccharide." This systematic review has been conducted on the basis of the key consideration of the PRISMA Statement-Preferred Reporting Items for the Systematic Review and Meta-analysis. Results: Hence, 163 potentially important abstracts and research topics have been discovered by electronic searches and three studies (3 RCTs) have been included. According to the outputs, any statistically significant differences have been not found between the rotary files and reciprocation (SMD 0.51, 95% CI [0.11, 0.90], p=0.011) (I2 = 49.5%; p=0.138) . Conclusion: Analyses indicated that instrumentation methods decreased the content of endotoxin from the root canals.